Host sharing by the honey bee parasites Lotmaria passim and Nosema ceranae - Tritschler, Manuel (John Wiley and Sons Inc., 2017)

(untitled) (Ecol Evol)
The trypanosome Lotmaria passim and the microsporidian Nosema ceranae are common parasites of the honey bee, Apis mellifera, intestine, but the nature of interactions between them is unknown. Here, we took advantage of naturally occurring infections and quantified infection loads of individual workers (N = 408) originating from three apiaries (four colonies per apiary) using PCR to test for interactions between these two parasites. For that purpose, we measured the frequency of single and double infections, estimated the parasite loads of single and double infections, and determined the type of correlation between both parasites in double infections. If interactions between both parasites are strong and antagonistic, single infections should be more frequent than double infections, double infections will have lower parasite loads than single infections, and double infections will present a negative correlation. Overall, a total of 88 workers were infected with N. ceranae, 53 with L. passim, and eight with both parasites. Although both parasites were found in all three apiaries, there were significant differences among apiaries in the proportions of infected bees. The data show no significant differences between the expected and observed frequencies of single‐ and double‐infected bees. While the infection loads of individual bees were significantly higher for L. passim compared to N. ceranae, there were no significant differences in infection loads between single‐ and double‐infected hosts for both parasites. These results suggest no strong interactions between the two parasites in honey bees, possibly due to spatial separation in the host. The significant positive correlation between L. passim and N. ceranae infection loads in double‐infected hosts therefore most likely results from differences among individual hosts rather than cooperation between parasites. Even if hosts are infected by multiple parasites, this does not necessarily imply that there are any significant interactions between them.